Evaluasi Waktu Start Up pada Proses Peruraian Stillage secara Anaerobik Menggunakan Reaktor Fixed Bed dengan Zeolit sebagai Media Imobilisasi - Wivina Diah Ivontianti; Wiratni Budhijanto; Siti Syamsiah (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Stillage was a waste containing high organic load and thus potentially as substrate anaerobic decomposition. However the complexity of the compounds contained therein has caused the decomposition process was slow.The study was conducted to evaluate the effect of substrate concentration to performance and the start up time required in fixed bed reactor with zeolite as immobilization media for stillage decomposition. The evaluation of the fixed bed reactor performance was executed by comparing experimental data and simulation result from the mathematical modelling as the standard under ideal condition for anaerobic stillage decomposition that has been compiled. The start up phase was conducted in the circulated batch system in two cycles with different substrate concentrations. Based on the evaluation, the first cycle with the substrate concentration of 11.900 mg sCOD/L required 7-10 days to start up. If the first cycle had been conducted in more than 10 days, the condition was not optimum and it led to the death of microorganism. In the second cycle start-up phase with concentration of the substrate of 17.600 mg/L sCOD in the reactor resulted in the failure of the system due to organic shock loading. From this study, it is obtained the substrate with low concentration, 10.000 mg/L was good to start up.